Positive Solutions of Nonlinear Fractional Differential Equations with Integral Boundary Value Conditions - J. Caballero; I. Cabrera; K. Sadarangani (Abstract and Applied Analysis)
We investigate the existence and uniqueness of positive solutions of the following nonlinear fractional differential equation with integral boundary value conditions, , , where , and is the Caputo fractional derivative and is a continuous function. Our analysis relies on a fixed point theorem in partially ordered sets. Moreover, we compare our results with others that appear in the literature.